2003
DOI: 10.1002/pros.10303
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide scan of Swedish families with hereditary prostate cancer: Suggestive evidence of linkage at 5q11.2 and 19p13.3

Abstract: Our results provide strong confirmatory evidence of linkage at 19q13.3 and 5q11.2. The lack of confirmation of linkage at several loci identified in other genome-wide scans emphasizes the need to combine linkage data between research groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…Remarkable, however, is a pattern of three of our loci on 19p, 15q and 1p, which were recently reported from a genomewide scan on Swedish HPC families. 30 This similarity may possibly support the hypothesis of a population based genetic heterogeneity.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Remarkable, however, is a pattern of three of our loci on 19p, 15q and 1p, which were recently reported from a genomewide scan on Swedish HPC families. 30 This similarity may possibly support the hypothesis of a population based genetic heterogeneity.…”
Section: Discussionsupporting
confidence: 55%
“…30 In the late-onset group of their sample, Wiklund et al observed a maximum hLOD score of 1.35 on 1p, 15 cM telomeric from the critical region in our scan. The coincidence of the two independent findings at 1p31 may indicate a new candidate region for hereditary prostate cancer.…”
Section: Discussionmentioning
confidence: 43%
“…The genomic location of human miR-449a is chromosome 5q11.2, a region identified as a susceptibility locus in a variety of malignancies, including prostate cancer (Pan et al, 2001;Wiklund et al, 2003). We found that miR-449a is frequently downregulated in prostate cancer tissues, relative to patientmatched control tissue.…”
Section: Introductionmentioning
confidence: 74%
“…miR-449a expression was lower in tumor tissue compared to normal patientmatched control tissue. The genomic location of human miR-449a is chromosome 5q11.2, a region identified as a susceptibility locus in prostate cancer (Pan et al, 2001;Wiklund et al, 2003). Loss of miR-449a, an endogenous HDAC-1 inhibitor, may promote aberrant expression of HDAC-1 in prostate cancer contributing to the etiology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The present author and colleagues are investigating the effect of functional selenoprotein SNPs on prostate cancer risk using DNA samples from 1400 prostate cancer cases and 800 age-and location-matched controls from the Swedish prostate cancer study (Wiklund et al 2003). Careful speciation work (Goenaga-Infante et al 2004, 2005 is also being extended to identify low-molecularweight Se species in body tissues and fluids and in Se-enriched yeast and plants.…”
Section: Current and Future Selenium-cancer Projectsmentioning
confidence: 99%